Patisiran for the treatment of patients with familial amyloid polyneuropathy - Rizk, M.; Tuzmen, S. (Prous Science, Sau-Thomson Reuters, 2019)
Onpattro, also commonly known as patisiran, is a small interfering RNA (siRNA) molecule packaged within a lipid nanoparticle and is transported into the cell to target transthyretin gene (TTR) messenger RNA (mRNA) by attaching to its complementary sequence. The target mRNA is degraded and both mutant and wild-type amyloid transthyretin (ATTR) protein production becomes suppressed. This drug was developed by Alnylam Pharmaceuticals to treat a rare disease called hereditary ATTR (hATTR) amyloidosis. This disease develops as a result of the deposition of toxic aggregates of misfolded TTR protein, and is progressive causing the affected individual to be bed-bound and to eventually die if left untreated. However, variable expressivity and incomplete penetrance cause carriers of TTR gene variants to be asymptomatic for a prolonged time. The heterogeneity of symptoms makes correct diagnosis of the disease difficult, therefore management of symptoms and proper treatment are delayed as a result. However, certain TTR variants are found in endemic or cluster regions, which facilitates their detection. In this review paper, different aspects of the drug are discussed in detail, including its preclinical and clinical studies, as well as its pharmacokinetic properties along with drug interactions leading to its approval by the U.S. Food and Drug Administration (FDA) and the European Medicines Agency (EMA).
Keywords: Patisiran; Onpattro; siRNA; Mutated transthyretin (TTR); TTR inhibitors; hATTR amyloidosis; Familial amyloid polyneuropathy; Gene therapy